Defining Aspects of Acute Lithiasic Cholecystitis: An integrative literature review (Research, Society and Development, 2024)
Introduction: Acute Cholecystitis (AC) is the result of obstruction of the cystic duct, often caused by the presence of gallstones. Its clinical presentation includes right upper quadrant pain, fever, and leukocytosis, and diagnosis relies on symptomatology, physical examination, and diagnostic tools. Due to its high prevalence and potentially fatal complications, this study aims to characterize lithiasic AC, highlighting its clinical, epidemiological, and pathophysiological aspects, as well as appropriate diagnosis and management. Methodology: This is an integrative review on lithiasic acute cholecystitis. Data were obtained from the Virtual Health Library (BVS), Scientific Electronic Library of Medicine (SciELO), and National Library of Medicine (PubMed) databases to answer the question formulated using the PICO strategy. Results and Discussion: AC is caused 95% of the time by biliary lithiasis, which has a prevalence of 10% in the general population. Gallstones are formed when there is an imbalance in the components of bile and precipitation of one or more of these components. The majority of patients affected by cholelithiasis are asymptomatic, but one of the recurrent complications is AC, characterized by inflammation of the gallbladder. For the diagnosis of AC, clinical suspicion must be confirmed through physical examination, laboratory, and imaging studies. Regarding treatment, cholecystectomy provides definitive cure, with an assessment of the need for antibiotic therapy. Concluding Remarks: Given its high prevalence, it is necessary to keep studies updated to allow continuous advances in diagnostic, therapeutic methods, and prevention of AC.